Introducing international relations - Sharp, Paul 1953- (Abingdon, Oxon, [England] Routledge, Taylor & Francis Group, 2018)
"This new textbook provides an accessible and lively introduction to international relations for students encountering the subject for the first time. Presenting complex ideas, concepts and arguments in a straightforward and conversational way, the textbook explains international relations from a diplomatic perspective, emphasizing co-existence in the absence of agreement, and developing students' ability to make sense of the current conditions of international uncertainty. Introducing students to the major theories and issues in international relations, each chapter: - is written to a common structure, dividing each topic into sections with learning objectives within each section to provide points of focus for students and instructors - includes extensive text box examples and short case studies for reflection and discussion - provides key terms, key takeaways and simple exercises which require short responses - offers a suggested list of further readings for those who wish to explore a topic further - is supported by a companion website which provides students and instructors with quizzes on terms and concepts, and includes updates on key cases and examples The first introductory textbook to take a diplomatic approach, this text is essential reading for all those looking to take their first steps into the study of international relations in an era of uncertainty"--Provided by publisher.
Introduction: why study international relations and other basic questions -- International theory, realism and power politics -- Liberalism and building world orders -- Constructivism, the English School, Feminism and other post-positivist theories of international relations -- Foreign policy -- International conflict and competition -- Military power and war -- International law, international organization, and human rights -- International trade and international production -- International and global finance -- International and regional integration and disintegration -- Natural resources, population, and the environment -- North-south gaps and old-new gaps -- Economic, human, and political development.
Includes bibliographical references and index.
Keywords: International relations